ON THE CULT OF A FEMALE DEITY AMONG THE EARLY NOMADS OF THE ARAL SEA REGION - Дарменов Р.Т (TARIXIY TADQIQOTLAR, 2025)
The article presents the results of archaeological research conducted by the A.Kh. Margulan Institute of Archaeology at the ancient settlement of Chirik-Rabat. In the course of excavations the materials were discovered that allow studying religious and ideological ideas of the population of the oasis of Chirik-Rabat and adjacent territories. The finds include anthropomorphic images and sculptures of female deities, which have a genetic connection with the agricultural cultures of southern Central Asia. By the end of the 4th c. BC, under the influence of changes in the socioeconomic situation and the formation of a new religious and worldview ideology, the production of terracotta figurines and sculptures began. This process coincides with the emergence of the ancient Khorezmian statehood, as well as with the the penetration of Hellenic culture and technological innovations into the south in the early 3rd century BC.